Blood Viscosity and Cerebral Blood Flow - Shirakura, Takuo; Tamura, Kousei; Kubota, Kazuo (Nihon Rōnen Igakkai zasshi, 1993)
It is well known that there is a close correlation between blood viscosity and blood flow. To clarify any relationship between blood viscosity and regional cerebral blood flow (rCBF) in the elderly, we simultaneously studied both CBF with PET (positron emission tomography) and blood viscosity with viscosimeter before and after phlebotomy in the elderly with various kinds of polycythemia. These subjects consisted of five male cases of secondary polycythemia due to pulmonary fibrosis, one male case of essential erythrocytosis (average age 66.6±4.6 years old) and one female case of stress polycythemia (47 years old). Before phlebotomy an increase in blood viscosity, decrease in rCBF and regional cerebral matablic rate of oxygen (rCMRO2) were observed in all cases. After phlebotomy (total amount of 800 to 1, 000ml) blood viscosity rapidly decreased, and both rCBF and rCMRO2 tended to increase. There was a significant negative or positive correlation between CBF and blood viscosity or rCMRO2, respectively. However, no increase in cerebral oxygen transport was observed in any subject after phlebotomy. It was noted that cerebral infarction is not infrequent among elderly visitors to Kusatsu spa, which is characterized by high temperature hot spring water. From the authors' observation of 23 cases of cerebral infarction encountered during the last five years, it is noteworthy that the disease tended to occur more frequently during midnight to morning, specially 3:00 to 6:00. Thus, to clarify the pathogenetic mechanism of the cerebral infarction occurring after bathing in hot spring water, we studied the changes in blood viscosity, blood pressure and coagulation-fibrinolytic system after bathing in hot spring water. The results obtained were as follows. After bathing in hot spring water (42-47°C for 3 to 10min, at 16:00), a significant elevation of blood viscosity was observed from 4:00 to 8:00 and a significant lowering of blood pressure from 20:00 to 8:00 compared with bathing in plain water. In addition, bathing in high temperature water resulted in a decrease in tPA (tissue-typed plasminogen activator) and an increase in PAI-1 (plasminogen activator inhibitor-1). An in vitro study using human umbilical vein endothelial cell (HUVEC) revealed that a high temperature during incubation stimulates secretion of PAT-1 into the blood stream from vascular endothelial cells. From these results it is speculated that hemoconcentration, vasodilatation and inhibition of the fibrinolytic system caused due to the thermal insulation effect of hot spring water might play some role in the pathogenetic mechanism of cerebral infarction, which tends to occur from midnight to the early morning in the elderly visitors.